A Review of Edward Luce's In Spite of the Gods: The Strange Rise of Modern India - Pritchett, Lant (Journal of Economic Literature, 2009)
India poses a development puzzle on a grand scale. Sixty years of electoral democracy, thirty years of rapid growth, and a number of world class institutions (such as the Institutes of Technology or Election Commission) have led to talk of India as a superpower in a league with the United States and China. Yet, on many fronts, India's indicators of human well-being (e.g., malnutrition, immunization) are at, or below, those of much poorer sub-Saharan African countries. Measures of the administrative capacity of the state on basics like attendance, performance, and corruption reveal a potentially “flailing state” whose brilliantly formulated policies are disconnected from realities on the ground. This review essay of Ed Luce's In Spite of the Gods attempts to articulate the puzzle that is modern India and pose questions about the development trajectory of a country whose fortunes will shape our century.